The Ground Zero Mosque Controversy: Implications for American Islam - Takim, Liyakatali (Religions, 2011)
The controversy surrounding the “ground zero mosque” is part of a larger debate about the place of Islam in U.S. public space. The controversy also reveals the ways in which the boundaries of American identity continue to be debated, often through struggles over who counts as a “real” American. It further demonstrates the extent to which Islam is figured as un-American and militant, and also the extent to which all Muslims are required to account for the actions of those who commit violence under the rubric of Islam. This paper will discuss how, due to the events of September 11, 2001, Muslims have engaged in a process of indigenizing American Islam. It will argue that the Park51 Islamic Community Center (or Ground Zero mosque) is a reflection of this indigenization process. It will go on to argue that projects such as the Ground Zero mosque which try to establish Islam as an important part of the American religious landscape and insist on the freedom of worship as stated in the U.S. constitution, illustrate the ideological battlefield over the place of Islam in the U.S. The paper will also examine the possible ramifications of building the Park51 Islamic Community Center including how this will shape the role that Islam plays in the socio-political lives America Muslims.